Measuring The Effectiveness of U-Dictionary in Increasing The Interest in Learning English Language Student At Madrasah Ibtidaiyah - Feren Fedora; Moh. Ferdi Hasan (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
In the current era of disruption, the need to learn English is very important, therefore several digital applications have been created to make learning English easier, especially for students. U-Dictionary is a popular English learning application that can be used as an option, therefore this research aims to analyze the effectiveness of using the U-Dictionary application in increasing students' interest in learning at Madrasah Ibtidaiyah and what students' perceptions are regarding the use of U-Dictionary in increasing interest in learning languages. English at Madrasah Ibtidaiyah. This research uses mixed methods. The data collection technique used in this research is a questionnaire. Data analysis used the paired t-test data analysis technique with the Shapiro-Wilk normality test. Meanwhile, the qualitative analysis uses content analysis. Based on the results of data analysis, it can be seen that the U-Dictionary application is effective in increasing students' interest in learning at Madrasah Ibtidaiyah with a significance value (<0.001). The results of the questionnaire regarding students' perceptions of using U-Dictionary, the majority of respondents had a fairly high level of use, a fairly high level of self-confidence, the ability to understand good English vocabulary, a fairly high level of interest in learning English, and felt that learning English is quite effective or very effective.